Dáwólé Yorubá - Franco, Leonardo Alvarez [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Abstract Dáwólé Yorubá is a work on research and development of a Game Design Document, a guide for the further creation of an electronic game, which script will be based on the myths of the Yoruba, a native people from Nigeria that is an important part in the Brazilian cultural background. The project is based on the assumption that games are capable of affect one's learning possibilities. To confirm that hypothesis, a poll was made on social networks, and through the obtained data was possible to ensure that the themes addressed in the project, such as history and mythology, were among the most quoted as learning objetcs by the interviewed players. There is a brief discussion on mythology and religion, a presentation of the Yoruba people and its myths and introduces theories by Huizinga and Crawford on why games are importants on a social context, and what reasons brings people to playing them. This paper presents a report on several aspects of the creation of a game. It defines elements of narrative, aesthetics and gameplay. All the important characters were detailed visual- and textually. The protagonist had a small sprite sheet created as a model. Some sketches of backgrounds and gameplay challenges were made, and two concept arts were developed. Furthermore, there is the detailed register on the making of a model ready to be used in stop motion animations, a style proposed to be used in the game cutscenes

Resumo Dáwólé Yorubá é o trabalho de pesquisa e desenvolvimento de um Game Design Document, um guia para a futura criação de um jogo eletrônico, cujo roteiro será baseado em mitos do povo iorubá, nativo da Nigéria e parte importante da formação cultural brasileira. O projeto partiu do pressuposto de que jogos são capazes de influenciar o aprendizado das pessoas. Para confirmar a hipótese, foi realizada uma pesquisa através de redes sociais e, através da análise dos dados obtidos, pode-se confirmar que os temas abordados pelo projeto, história e mitologia, estão entre os mais citados como objetos de aprendizado pelos jogadores entrevistados. Traz uma pequena discussão sobre mitologia e religião, conceitua o povo e os mitos iorubás, e apresenta teorias de Huizinga e Crawford sobre o porque de o jogo ter papel importante na sociedade, e quais os motivos que levam as pessoas à sua prática. Este documento apresenta um registro de ideias sobre diversos aspectos da criação de um jogo. Define elementos narrativos, estéticos, e de jogabilidade. Todos os personagens importantes foram detalhados visual e textualmente. O principal teve uma pequena sprite sheet criada como modelo. Alguns esboços de cenários e desafios de jogabilidade foram feitos, e duas artes conceituais foram desenvolvidas. Além disso, traz também a produção detalhada de um boneco pronto para ser usado em animações stop motion, estilo proposto para compor as cenas de animação do jogo
Keywords: Jogos eletronicos; Mitologia; Cultura afro-brasileira; Orixas; Games